2021
DOI: 10.1084/jem.20210759
|View full text |Cite
|
Sign up to set email alerts
|

A human mutation in STAT3 promotes type 1 diabetes through a defect in CD8+ T cell tolerance

Abstract: Naturally occurring cases of monogenic type 1 diabetes (T1D) help establish direct mechanisms driving this complex autoimmune disease. A recently identified de novo germline gain-of-function (GOF) mutation in the transcriptional regulator STAT3 was found to cause neonatal T1D. We engineered a novel knock-in mouse incorporating this highly diabetogenic human STAT3 mutation (K392R) and found that these mice recapitulated the human autoimmune diabetes phenotype. Paired single-cell TCR and RNA sequencing revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 66 publications
0
29
2
Order By: Relevance
“…3 a, b). To further study the library depth effects on AMULET’s performance, we applied it on snATAC-seq data with different library depth: (1) publicly available mouse CD45 + cells [ 16 ] and innate lymphoid cells (ILCs) data [ 17 ] and (2) down-sampled PBMC1 and PBMC2 samples at 5% increments starting at 50%. To quantify AMULET’s performance, we simulated multiplets in each sample by randomly selecting nuclei pairs and used them to calculate recall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 a, b). To further study the library depth effects on AMULET’s performance, we applied it on snATAC-seq data with different library depth: (1) publicly available mouse CD45 + cells [ 16 ] and innate lymphoid cells (ILCs) data [ 17 ] and (2) down-sampled PBMC1 and PBMC2 samples at 5% increments starting at 50%. To quantify AMULET’s performance, we simulated multiplets in each sample by randomly selecting nuclei pairs and used them to calculate recall.…”
Section: Resultsmentioning
confidence: 99%
“…The islet 1, islet 2, and pooled PBMC datasets are publicly available from the Gene Expression Omnibus (GEO) repository (GSE165212 ) [25], https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE165212. Immune cell datasets from mice analyzed during the current study are available from the Gene Expression Omnibus (GEO) repository (GSE173415 [16], GSE149622 [17]), https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE173415 and https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE149622. Documentation and source code files for the AMULET framework are freely available under a GPL V3 license on GitHub at https://github.com/UcarLab/AMULET [26].…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, STAT3 signaling was repressed in Stages I and II, but not in Stages IIIC and IV compared to Benign groups. Gain of function STAT3 mutations have been shown to promote diabetes, while inhibition of the JAK kinase upstream of STAT3 has been shown to control lymphoproliferation in a diabetes patient with a STAT3 gain of function mutation [ 45 , 46 ]. STAT3 was reported to be upregulated in early-stage endometrial cancer, and inhibition of its signaling pathway has been shown to repress endometrial cancer stem cells and tumor growth [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in STAT3 are also implicated in the development of autoimmune diseases, including type 1 diabetes [ 153 ]. Recently, a mouse model heterozygous for STAT3 K392R gain-of-function mutation was generated [ 154 ]. The authors demonstrated that STAT3 K392R mutation in CD8+ T cells counteracts exhaustion, increases cytotoxicity, and can accelerate the development of T1D.…”
Section: Stat3 Mutations Linked To T-cell Memorymentioning
confidence: 99%